Assessment of hyposalivation, xerostomia, and oral health-related quality of life in polymedicated patients - Marques, João Gato (2021)
To investigate the self-reported impact of hyposalivation/xerostomia on Oral Health-Related Quality of Life (OHRQoL) reported by polymedicated patients and evaluate the association between hyposalivation/xerostomia and OHRQoL. A cross-sectional observational study was performed on 40 polymedicated patients selected from the Clínica Dentária Egas Moniz. The subjects signed a consent form, answered a questionnaire to assess xerostomia via the Summated Xerostomia Inventory (SXI-PL) and The Portuguese short version of the Oral Health Impact Profile Questionnaire (OHIP-14sp), and underwent sialometry evaluation. Patients with hyposalivation showed higher scores of SXI-PL (8.60 ± 2.56) and OHIP-14sp (16.0 ± 15.8). These findings suggest an association between hyposalivation and SXI-PL and OHIP-14sp scores (p < 0.05).